Improved molecular typing of toxigenic Clostridium difficile strains affecting animal and human health. Issue Volume 1(2019)Issue A (8th March 2019) - Nowak-Roddy, Madelyn; McKenna, James; Fairley, Derek
Abstract : Clostridium difficile is a Gram-positive, spore forming bacterium, which remains a formidable pathogen as the etiological agent of C. difficile infection (CDI). Substantial effort goes into diagnosis of CDI and characterisation of circulating toxigenic C. difficile strains for epidemiology and infection prevention and control. Currently, molecular typing of C. difficile requires 9 days following diagnosis through PCR ribotyping and multilocus variable number tandem repeat (VNTR) analysis. There is a need for more rapid typing methods to investigate possible linkage between CDI cases in healthcare settings. This study developed a one-step, closed tube real-time PCR and high resolution melt (HRM) assay targeting the intergenic spacer region (ISR) and several VNTR loci, with results generated in 2.5 h. The discriminatory power of the PCR-HRM assay was investigated by typing previously characterised toxigenic clinical and animal C. difficile isolates ( n =90). Through comparison of HRM profiles targeting the ISR of isolates belonging to 17 PCR ribotypes, 13 HRM genotypes were recognised with 11 PCR ribotypes resolved from each other. Using correlation between HRM data and known VNTR repeat numbers at the B7, C6 and G8 loci, VNTR repeat numbers for isolates could be predicted within an average absolute difference of 1.8 at the B7 locus, 2.1 at the C6 locus, and 2.5 at the G8 locus. These results suggest that a PCR-HRM assay with a multilocus panel targeting ISR and selected VNTR loci could form part of an improved molecular typing scheme for toxigenic C. difficile strains that is faster than currently available methods.